Optimizing 3D antenna arrays and ground station distribution for satellite communication - Arruda, Téssio Perotti (2024)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2024.